Evaluasi Penggunaan Layanan Koleksi E-Resources Menggunakan Standar Indikator Kinerja (ISO 11620:2014) Di Perpustakaan Nasional RI - Indreswari Nurmalia; Aziz Kustiyo; Sulistyo Basuki (Perpustakaan IPB, 2016)
One of library’s most important element of the library is collection. The rise information and technology, has improved library needs to transforms into digital era. Library users preferred e-resources collections. The National Library of Indonesia (NLI) realized e-resources collection has become one of the primary collection. During these five years, there are not enough research about usage of e-resources collection services evaluation. This research took evaluation of the usage of e-resources collection services with a quantitative approach of the ISO 11620:2014 as general standard for library performance indicators. ISO 11620:2014 is a statement of symbol, numeric, and verbal that is obtained through the library statistics and data that is used to characterized the library performance indicators. There are 6 (six) performance indicators that are used as benchmark in assesing how far e-resources collection is used in The NLI on 2014-2015. Those 6 (six) indicators are : (1) The percentage of e-resources collection that is not used); (2) the number of content unit downloaded per capita; (3) the number of visitors that join the e-resources training; (4) the expense of the e-resources collection procurement; (5) the percentage of expenditure on the provision of information for the collection of e-resources; (6) Percentage of library staff who provide the guidance of the e-resources collection services for. This research found that e-resources usage collections services in The NLI is not optimized. E-resources collections service has not maximized for following reasons. First, The NLI’s e-resources is in balanced referring to covered subjects. The high e-resources collections that were not used by user, only 3% of the whole e-resources collections are used by users. Although, the level of content downloaded unit per capita for each e-resources collections decreased from the previous year. E-journals downloaded are more higher than the e-books and e-videos downloaded from whole e-resources collections. In 2015, the number e-books and e-video downloaded are less than 5 per 1000 user. PROQUEST download decreased from 2.7 to 1.9 for all users served. These conditions was caused by lack of e-resources development policy that becomes controlling in the process of collection management at the National Library of Indonesia. NLI needs to improve the e-resources development a primary missions to create a great form of national collections. Second, NLI need to set priority in providing technology based services. E-resources training and promotion are also need to set up as priority to colleges that have limited infrastructure and internet access. There are a large number user can be a potential gateway to increasing e-resources usage. This research found users were trained at the NLI’s e-resources has decreased in 2015. There was about 3 users per 1000 the NLI’s users in the previous year. Third, the level of the percentage of staff who provide training increased by 12.34% from the previous year. Although there was improvement the percentage of the GCC staff training is still very small compared with the number of staff at service center. Librarian’s competencies also needed to improve e-resources training in NLI. Librarian must have competenciies as much skill in providing information services in technology, has skill in searching strategy using e-resources. The research also found evaluation of e-resources usage at NLI will increase. Fourth, in terms of budget indicators issued for the provision of information in the form of a collection of e-resources shows the results are quite positive. Costs incurred for the provision of e-resources collections always increase every year. The research recommended further research related to the application of e-resources system performance measurement standards. It is important for the evaluation of performance of e-resources development at NLI to improve performance even better in the future.Key words: e-resources, usage evaluation, National Library of Indonesia (NLI), ISO 11620